Al-Qadi's Poetic Wisdom as a Catalyst for the Sustainable Preservation of Saudi Arabia's Coffee Culture - Kurniawan Arif Maspul (Innovative: Journal Of Social Science Research, 2023)
This article embarks on a captivating journey that delves deep into the intricate relationship between the profound local wisdom expressed in the poetic works of Muhammad Abdullah Al-Qadi and the vibrant coffee culture of Saudi Arabia. Beyond being a beverage of cultural significance, coffee holds a pivotal role in shaping the sustainable future of Saudi Arabia's agricultural practices and cultural heritage. Al-Qadi's poetic masterpiece, "Al-Qahwa" serves as a testament to the enduring allure of coffee in Arab culture, while artfully capturing the very essence of Saudi Arabia's rich coffee heritage in coffee value chain. Through a meticulous exploration of Al-Qadi's evocative verses and their deeply resonant impact on the people of Saudi Arabia, this article uncovers the profound connection between coffee, sustainability, and the tapestry of human emotions, communal bonds, and personal relationships. Furthermore, it acknowledges Al-Qadi's indelible influence on subsequent poets and the poem's remarkable role in shaping the literary landscape. Lastly, this article highlights the importance of sustaining Saudi Arabia's coffee culture, emphasizing the need for responsible agricultural practices and cultural preservation efforts.